A Double-Track Pathway to Fast Strategy in Humans and Its Personality Correlates - Gutiérrez, Fernando; Peri, Josep M.; Baillès, Eva; Sureda, Bárbara; Gárriz, Miguel; Vall, Gemma; Cavero, Myriam; Mallorquí, Aida; Ruiz Rodríguez, José (Frontiers in Psychology, 2022)
The fast-slow paradigm of life history (LH) focuses on how individuals grow, mate, and reproduce at different paces. This paradigm can contribute substantially to the field of personality and individual differences provided that it is more strictly based on evolutionary biology than it has been so far. Our study tested the existence of a fast-slow continuum underlying indicators of reproductive effort —offspring output, age at first reproduction, number and stability of sexual partners— in 1,043 outpatients with healthy to severely disordered personalities. Two axes emerged reflecting a double-track pathway to fast strategy, based on restricted and unrestricted sociosexual strategies. When rotated, the fast-slow and sociosexuality axes turned out to be independent. Contrary to expectations, neither somatic effort —investment in status, material resources, social capital, and maintenance/survival— was aligned with reproductive effort, nor a clear tradeoff between current and future reproduction was evident. Finally, we examined the association of LH axes with seven high-order personality pathology traits: negative emotionality, impulsivity, antagonism, persistence-compulsivity, subordination, and psychoticism. Persistent and disinhibited subjects appeared as fast-restricted and fast-unrestricted strategists, respectively, whereas asocial subjects were slow strategists. Associations of LH traits with each other and with personality are far more complex than usually assumed in evolutionary psychology.